Empresses and Augustae as wives, paramours and mistresses (5th–11th centuries) - Nikolaou, Katerina (Byzantinoslavica-Revue internationale des Etudes Byzantines, 2017)
The authors who documented the lives of emperors –with very few exceptions, such as Procopius and Michael Psellos– were not particularly interested in their private or romantic aff airs. Occasionally they might mention imperial wives by name, but they would make extensive references to empresses only when their actions infl uenced political developments. What they neglected to do, however, was to approach those illicit incidents from a feminine point of view as well; as a result, certain questions emerge, revolving around the central reference point of the women concerned, both as parts of the regularity of marital relations and as agents leading to the disruption or circumvention. The aim of this study is to present, with the use of telling references from the above-mentioned sources, the distinct and/or interlocked “love” parts played by Byzantium’s crowned women, to attempt their categorization and to draw certain broad conclusions conerning their roles as wives, paramours and mistressess.